As condições de vida dos arranjos domiciliares brasileiros, medidas pela renda e por indicadores multidimensionais em 2009 - Daniane Christie Alves Pires (2012)
This study evaluates the differences in living conditions of Brazilian families, as the living arrangement exists, through income and multidimensional objective and subjective indicators. Through the Household Budget Survey (HBS) conducted by the Brazilian Institute of Geography and Statistics (IBGE) between the years 2008 and 2009, defines the types of living arrangements that exist in Brazil - according to their demographic and economic - and verifies whether and how the composition of these arrangements is associated with living conditions, according to each indicator by using the technique known as microeconometric Ordered Logit. Thus, identifying the differences between the living conditions of the living arrangements when measured by income and by multidimensional indicators is encouraged to discuss what needs to change the focus of public policies of the individual to the family and complement the theoretical foundation of the policies in question that focus on income with consideration of the various aspects involved in the condition of life.